2016
DOI: 10.1093/molbev/msw214
|View full text |Cite
|
Sign up to set email alerts
|

Transmission between Archaic and Modern Human Ancestors during the Evolution of the Oncogenic Human Papillomavirus 16

Abstract: Every human suffers through life a number of papillomaviruses (PVs) infections, most of them asymptomatic. A notable exception are persistent infections by Human papillomavirus 16 (HPV16), the most oncogenic infectious agent for humans and responsible for most infection-driven anogenital cancers. Oncogenic potential is not homogeneous among HPV16 lineages, and genetic variation within HPV16 exhibits some geographic structure. However, an in-depth analysis of the HPV16 evolutionary history was still wanting. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
89
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(101 citation statements)
references
References 90 publications
10
89
0
2
Order By: Relevance
“…In addition, we describe an increment of HPV16_A4 variants in glandular cancer types, 28% for ADC and 25% for ADSC, as reported in other studies including African, Central‐South American and Asian isolates (18% of 50 ADC) . Regarding variation in HPV16 lineage prevalence depending on the geographical origin of the samples, our results largely confirm the best data available showing a large dominance of HPV16_A1‐3 variants in Europe, the virtually exclusive presence of HPV16_B and C variants in Africa, the increased prevalence of HPV16_A4 variants in Asia and the enrichment of HPV16 D variants in the Americas.…”
Section: Discussionsupporting
confidence: 89%
“…In addition, we describe an increment of HPV16_A4 variants in glandular cancer types, 28% for ADC and 25% for ADSC, as reported in other studies including African, Central‐South American and Asian isolates (18% of 50 ADC) . Regarding variation in HPV16 lineage prevalence depending on the geographical origin of the samples, our results largely confirm the best data available showing a large dominance of HPV16_A1‐3 variants in Europe, the virtually exclusive presence of HPV16_B and C variants in Africa, the increased prevalence of HPV16_A4 variants in Asia and the enrichment of HPV16 D variants in the Americas.…”
Section: Discussionsupporting
confidence: 89%
“…It is now clear that such interbreeding did leave traces in contemporary modern humans outside Africa at the level of a few percent of the genome, with regional and inter-individual variation probably due to repeated interbreeding with Neanderthals and Denisovans [5 ,11 ,12 ]. Contact between human lineages is also revealed by other lines of evidence including the oral commensal microbe Methanobrevibacter oralis from a Spanish Neanderthal pointing to his ancestors having had contact with an African strain presumably from the AMH in the Levant c. 126 kya [13], and the sexually transmitted oncogenic human papillomavirus 16 which shows strains having split c. 450 kya mirroring the divergence between Neanderthals and AMH, but later with the Neanderthal strain re-infecting AMH after c. 120 kya [14]. Leaving aside the functional relevance of these genomic introgressions for now, what they overwhelmingly highlight is the interwoven histories of the human lineages within and outside Africa during the last half million years.…”
Section: The Human Treementioning
confidence: 86%
“…[94] We can obtain convincing evidence of an anticancer role for vitamin D 3 in humans from a recent vitamin D 3 , calcium randomized clinical trial using supplements, [95] along with a pooled analysis of randomized trails, [96] and a prospective cohort study [97] because they showed significant reductions in their all-cancers risk. Intriguingly, Neanderthals gave some of the Europeans HPV16A, [98] so that this ancestry population had a "head start" for increasing their incidences of cancer over recent decades from indoor work and decreasing levels of vitamin D 3 .…”
Section: Discussionmentioning
confidence: 99%